Differential antagonism of Ras biological activity by catalytic and Src homology domains of Ras GTPase activation protein. - Clark, G J (1993)
Ras p120 GTPase activation protein (GAP), a cytosolic protein, is a negative mediator and potential downstream effector of Ras function. Since membrane association is critical for Ras function, we introduced the Ras membrane-targeting signal (a 19-residue peptide ending in CAAX, where C = cysteine, A = aliphatic amino acid, and X = any amino acid) onto the GAP N-terminal Src homology 2 and 3 and the C-terminal catalytic domains (designated nGAP/CAAX and cGAP/CAAX, respectively) to determine the role of membrane association in GAP function. cGAP/CAAX and full-length GAP/CAAX, but not GAP or nGAP/CAAX, exhibited potent growth inhibitory activity. Whereas both oncogenic and normal Ras activity were inhibited by cGAP/CAAX, nGAP/CAAX, despite lacking the Ras binding domain, inhibited the activity of oncogenic Ras without affecting the action of normal Ras. Altogether, these results demonstrate that membrane association potentiates GAP catalytic activity, support an effector function for GAP, and suggest that normal and oncogenic Ras possess different downstream interactions.